Richard Nixon and the Vietnam War the end of the American century - Schmitz, David F. (Vietnam--America in the war years, 2014)
In Richard Nixon and the Vietnam War, David F. Shmitz provides students of US history and the Vietnam era with an up-to-date analysis of Nixon's Vietnam policy in a brief and accessible book that addresses the main controversies of the Nixon years. Richard Nixon came into office seeking a decisive victory in Vietnam, and expanded the war in hopes of upholding a policy of "containment," protecting America's credibility, and defying the growing antiwar movement. However, by 1971 the president was forced to significantly de-escalate the American presence and seek a negotiated end to the war. Aided by recently declassified documents, Schmitz provides a comprehensive analysis of Nixon's Vietnam policy during the first years of his administration, clearly demonstrating that Nixon pursued military victory and providing a new periodization for our understanding of the Vietnam War.